Pengaruh Kesadaran Konsumen Halal Food Supply Chain Management terhadap Minat Beli Konsumen (Studi Kasus UMKM Makanan Sekitar Kampus II UINSU) - Muhammad Rifki Damanik; Supardi Supardi; Siti Aisyah (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
Halal supply chain management is an integration of business processes from an initial supplier who then provides products, services, and information that can add an added value to final consumers in accordance with the rules of Islamic teachings, namely the Al-Quran and Sunnah. The purpose of this study was to determine the effect of consumer awareness of halal food supply chain management on consumer buying interest. The method used is a qualitative method by distributing questionnaires to respondents. The sample used is UINSU students. The results of the study indicate that Halal Supply management has an effect on consumer buying interest.